Next‐generation technologies and data analytical approaches for epigenomics. (10th December 2013) - Mensaert, Klaas; Denil, Simon; Trooskens, Geert; Van, Wim; Thas, Olivier; De, Tim; O'Hagan, Heather; Tang, Winnie
<x xml:space="preserve">Abstract</x> Epigenetics refers to the collection of heritable features that modulate the genome–environment interaction without being encoded in the actual DNA sequence. While being mitotically and sometimes even meiotically transmitted, epigenetic traits often demonstrate extensive flexibility. This allows cells to acquire diverse gene expression patterns during differentiation, but also to adapt to a changing environment. However, epigenetic alterations are not always beneficial to the organism, as they are, for example, frequently identified in human diseases such as cancer. Accurate and cost‐efficient genome‐scale profiling of epigenetic features is thus of major importance to pinpoint these "epimutations, " for example, to monitor the epigenetic impact of environmental exposure. Over the last decade, the field of epigenetics has been revolutionized by several innovative "epigenomics" technologies exactly addressing this need. In this review, we discuss and compare widely used next‐generation methods to assess DNA methylation and hydroxymethylation, noncoding RNA expression, histone modifications, and nucleosome positioning. Although recent methods are typically based on "second‐generation" sequencing, we also pay attention to still commonly used array‐ and PCR‐based methods, and look forward to the additional advantages of single‐molecule sequencing. As the current bottleneck in epigenomics research is the analysis rather than generation of data, the basic difficulties and problem‐solving strategies regarding data preprocessing and statistical analysis are introduced for the different technologies. Finally, we also consider the complications associated with epigenomic studies of species with yet unsequenced genomes and possible solutions. Environ. Mol. Mutagen. 55:155–170, 2014. © 2013 Wiley Periodicals, Inc.